2013
DOI: 10.1073/pnas.1315760110
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for at least six Hox clusters in the Japanese lamprey ( Lethenteron japonicum )

Abstract: Significance Lampreys and hagfishes (cyclostomes) are the only living group of jawless vertebrates and therefore are important for the study of vertebrate evolution. We have characterized Hox clusters in the Japanese lamprey ( Lethenteron japonicum ), and shown that it contains at least six Hox clusters as compared with four Hox clusters in tetrapods. This suggests that the lamprey lineage has undergone an additional round of genome duplication compared with tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
212
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(230 citation statements)
references
References 38 publications
17
212
1
Order By: Relevance
“…Although initial studies concluded that the agnathan/gnathostome divergence occurred after the 2 rounds of genome duplication early in vertebrate evolution, 28,40 recent study of Hox genes in the Japanese lamprey has led to the suggestion that genome duplications may have occurred independently in the lamprey lineage. 29 This could also account for the identification of only 2 tenascins in the Japanese lamprey. The problems associated with determining the phylogenetic relationships of the lamprey tenascin sequences with each other and to other tenascins might also be accounted for by the fact that the lamprey genomes analyzed to date have unusually high GC content, which may bias the amino acid sequences of encoded proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Although initial studies concluded that the agnathan/gnathostome divergence occurred after the 2 rounds of genome duplication early in vertebrate evolution, 28,40 recent study of Hox genes in the Japanese lamprey has led to the suggestion that genome duplications may have occurred independently in the lamprey lineage. 29 This could also account for the identification of only 2 tenascins in the Japanese lamprey. The problems associated with determining the phylogenetic relationships of the lamprey tenascin sequences with each other and to other tenascins might also be accounted for by the fact that the lamprey genomes analyzed to date have unusually high GC content, which may bias the amino acid sequences of encoded proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Neither the 2012 assembly for the sea lamprey (Smith et al 2013) nor the 2013 assembly for the Japanese lamprey (Mehta et al 2013) fully meet the criterion, however. It should be emphasized that the missing data from the 2012 sea lamprey assembly are not because of programmed loss of DNA during development (Smith et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most direct In the article describing the whole genome assembly for the Japanese lamprey (Mehta et al 2013), the organism is referred to as Lethenteron japonicum. However, the downloaded version of the database describes each entry as Lethenteron camtschaticum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility could be that the [Ser 12 ]SS-14 variant is a product of an SS5 gene because, as has been mentioned above, SS5 and SS1 peptides are structurally very similar. Another possibility could be that it is a duplicate that arose in the recently proposed third lamprey-specific tetraploidization (Mehta et al 2013).…”
Section: Other Ss-related Peptidesmentioning
confidence: 99%